Analisis Penggunaan Frasa Adjektival dan Frasa Preposisional pada Teks Sejarah “Candi Borobudur” dalam World History Encyclopedia - Muadzin Muadzin; Nurul Liza Aulia Rahmi; Shabira Millatina; Shalshabila Naela Azzahra; Yogiana Zahwa Walidaini; Dyah Prabaningrum; Asep Purwo Yudi Utomo; Yanuar Bagas Arwansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
A phrase combines words with one function, and its use is essential in language. Many phrases were discovered in various media, one of which is in the historical text of Borobudur Temple, published in the World History Encyclopedia. This research aims to discover the category or grouping of phrases in historical texts, especially adjectival phrases and prepositional phrases. The method in this research is descriptive qualitative with a qualitative approach that produces descriptive data in the form of written words. The research results show that there are eight adjectival phrases and fifteen prepositional phrases in the historical texts studied. “Very close” is one of the adjectival phrases found in the historical text, while “Toward the northwest” is one of the prepositional phrases in historical text. This research aims to understand the use of adjectival phrases and prepositional phrases in a sentence to make effective sentences.